APPLICATION OF RECOMMENDED WEIGHT LIMIT (RWL) AND LIFTING INDEX (LI) TO ANALYZE PHYSICAL AND MENTAL LOAD (Case Studies: PT. KIMIA FARMA (PERSERO) PLANT BANDUNG) - Anwar Rijali; Maulana, Sendy; Dwi Ardiansyah, Redi; Ridwan, Muhammad; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
In a company, every single worker has different both duties and responsibilities, and each activity carried out will produce workload apart. The lifting, moving and lowering by manually is a lot of done by workers (man power). This research aims to determine the workload, both physically and mentally in the manual material handling activity at PT. Kimia Farma Plant Bandung which considers health and safety factors for operators. For propose to discover workload which exists in the material handling manual activity by measurements using the Recommended Weight Limit.(RWL).and Lifting Index (LI).method. Based on results obtained, the starting method of LI was 9.17. This indicates that lifting boxes activity by raw material warehouse officers poses a high risk of injury. For decreasing risk, the way lifting method have to change. As for the suggestion of tighten loads, don't over bending and reduced from 4 to 3 boxes only for stacking position. For suggestion method of Lifting Index was 3,59. The suggestion lifting method is better when we compared it with the old one. Seen from the decrease in the Lifting Index value of the old method when compared with the suggestion.